PSO BASED INTUITIONISTIC FUZZY OPTIMIZATION - A, MAHESWARI.; S, KARTHIKEYAN.; M, PALANIVELRAJAN.; A, SHUNMUGALATHA. (International Journal of Mathematical Archive, 2018)
Modeling of real life problems involving optimization process rolls out to be a multi-objective programming problem.Â  In order to optimize a linear programming model, numerous approaches have been suggested so far. Problems of decision making with re......